Modeling the Cordilleran Ice Sheet - Robert, Barry (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTA time-dependent ice flow model is used to provide detailed reconstructions of ice growth and retreat for the southern portion of the Late Wisconsinan Cordilleran Ice Sheet. The two-dimensional, time-dependent model provides ice surface elevations and flow directions at a grid spacing of 15 km. Input to the model includes subglacial topography, a net mass balance function, and two ice flow parameters. The net mass balance function uses a polynomial equation to estimate equilibrium line altitude (ELA) across the study area. A quadratic equation is then used to provide net mass balance values as a function of elevation relative to the ELA. Late Wisconsinan glacial conditions are simulated by systematically lowering the ELA. The general timing of the model ice advance and retreat is tested against radiocarbon dated localities which place limits on the ice sheet's areal extent for different times during the Late Wisconsinan glaciation. In addition, glacial-geologic evidence directly attributable to the latest Cordilleran Ice Sheet is used in assessing the model reconstructions. Results from these experiments show that an ice growth and retreat chronology consistent with the limiting radiocarbon dates can be generated using the model, and provide information on flow directions and ice growth and retreat patterns.